TAMBOR DE CRIOULA COMO PRESSUPOSTO PARA A IMPLEMENTAÇÃO DA LEI 10.639/2003: um estudo de caso na Unidade de Educação Básica Professora Rosália Freire - FREITAS, Marcos Aurelio dos Santos (2021)
The research deals with the Creole Drum, as a teaching content that can be inserted in the curriculum of schools in Maranhão, for the implementation of Law nº 10.639/2003. The field of research investigated was a municipal school in the city of São Luís, called: " Basic Education Unit Professor Rosália Freire ". to include it as teaching content, in a Notebook of Didactic Orientations that contemplates Afro- Brazilian and African History and Cultural". Teaching content, through a Book of Didactic Orientations that contemplate the Afro-Brazilian and African History and Culture"? The Dissertation is divided into three parts, namely: bibliographic, empirical and a proposal of applicability. In the bibliographic part, sections on Education for Ethnic-Racial Relations and on the Tambor de Crioula, as an Afro-Maranhense manifestation, are described and substantiated. In the empirical part, we discuss the characterization of UEB Professor Rosália Freire, the course of the research methodology and the analyzes and interpretations of the research participants. Then, a proposal for an educational product was presented, through the Didactic Guidelines Notebook, entitled: "Drum of Crioula and Law nº 10.639/03 in Basic Education". The Notebook is composed of six didactic and pedagogical lessons. Due to Covid-19, it was not possible to apply the educational product in the selected school for the research. Therefore, we rely on Normative Instruction No. 04/2020/PPGEEB/UFMA, which makes the applicability of the product optional. The main bibliographic references used were: Ferretti (2002), Gomes (2012), Munanga (2012), Laraia, (2004), Nogueira (2012), Rocha (2014), among others. The data collection instruments used were systematic observation and semi-structured interviews with the school manager - in person - and two teachers from the 4th and 5th grade classes of Elementary School - remotely. We concluded, through the research, materialized in the Didactic Guidelines Book that the Creole Drum contributes as an ethnic and cultural instrument of the Afro-Maranhense population, and can be inserted in school spaces in compliance with Law nº 10.639/03.